Mobility, prosthesis use and health-related quality of life of bilateral lower limb amputees from the 2008 Sichuan earthquake. (February 2019) - Li, Wing Sum; Chan, Sze Ying; Chau, Wai Wang; Law, Sheung-wai; Chan, Kai Ming
Background: The 2008 Sichuan Earthquake resulted in many amputees, yet due to the rare incidence, few studies have explored the rehabilitation outcomes and quality of life of bilateral lower limb amputees after major natural disasters. Objectives: To evaluate rehabilitation outcomes of 17 young and adult bilateral lower limb amputees under the StandTall rehabilitation programme and to identify factors associated with successful functional recovery of bilateral amputees after large-scale disasters. Study Design: Cross-sectional study. Methods: Mobility (amputee mobility predictor), prosthesis use (Houghton Scale) and health-related quality of life (Trinity Amputation and Prosthesis Experience Scale, Short Form 12) were evaluated through questionnaires and performance-based assessments. Means of scores were compared using T -tests. Results: Subjects with bilateral through-knee or transtibial amputations had less activity restriction ( p  < 0.01) and higher mobility ( p  = 0.03). Subjects using prostheses more than 50% waking time had better general adjustment ( p  = 0.02) and less functional restriction ( p  = 0.01). Exercise and education were associated with higher mobility ( p  = 0.06) and mental quality of life, respectively ( p  = 0.09). Conclusions: Amputation level and knee joint salvage, prosthesis use, exercise and education were associated with better rehabilitation outcomes including ambulation, adjustment and quality of life in bilateral lower limb amputees from the 2008 Sichuan Earthquake. Clinical relevance: The study examined a unique group of traumatic bilateral lower limb amputees who were young and healthy before having traumatic amputations from a single episode of natural disaster. The factors associated with better functional recovery after the earthquake were investigated and may support future development of post-disaster rehabilitation strategies for bilateral lower limb amputees.